Managing information technology (Pearson/Prentice Hall, 2005)
"Managing Information Technology, 5/E is a comprehensive guide to the information technology management techniques that are vital to a successful career as a manager. This edition has been thoroughly updated to reflect rapid changes in information technology and the latest business applications. It contains an extensive collection of case study options (34 cases), making it especially customizable for instructors in MBA programs. New features in this edition include a complete Data Resource chapter that provides a “big picture” look at issues associated with managing an organizations data. In addition to the award-winning ERP case, NIBCOs “Big Bang,” this edition includes several new cases, including the creation and operation of a Web-based business; leveraging SAP for supply chain management; making an outsourcing decision in a midsized manufacturing company; integrating information technology rapidly after a merger; and sharing services throughout a multinational firm. This edition also contains expanded e-business coverage, as well as insight into increasingly strategic technologies such as Linux, XML, .NET, J2EE, Bluetooth, and wireless LANs. Also included: a full chapter on IT project management, one of today's most sought-after skills for new employees."--pub. desc